Effect of C1‐Esterase‐inhibitor in angiotensin‐converting enzyme inhibitor‐induced angioedema. (13th January 2015) - Greve, Jens; Bas, Murat; Hoffmann, Thomas K.; Schuler, Patrick J.; Weller, Patrick; Kojda, Georg; Strassen, Ulrich
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The study objective was to generate pilot data to evaluate the effectiveness and safety of C1‐esterase‐inhibitor concentrate (C1‐INH) compared to standard treatment in patients with angiotensin‐converting enzyme inhibitor (ACEi)‐induced angioedema affecting the upper aerodigestive tract. Study Design Proof‐of‐concept case series with historical control. Methods Adult patients with angioedema in the upper aerodigestive tract presenting to the emergency department were included. After establishing the diagnosis of ACEi‐induced angioedema based on patient history and thorough clinical examination, all patients were administered 1, 000 international units (IU) of C1‐INH intravenously. A historical control group consisting of adult patients with ACEi‐induced angioedema who had been treated with intravenous corticosteroids and antihistamines at the same institution over the past 8 years was used for comparison. The most important parameters assessed were the time to complete resolution of symptoms and the need for intubation or tracheotomy. Results Ten patients were included in the C1‐INH group and 47 in the corticosteroid/antihistamine group. The time to complete resolution of symptoms was considerably longer in the historical control group (33.1 ± 19.4 hours) than in the C1‐INH group (10.1 ± 3.0 hours). No intubation or tracheotomy was needed in the C1‐INH group (0/10 patients), whereas three out of the 47 historical controls required tracheotomy and two were intubated (5/47). Conclusion The results suggest a role for C1‐INH as an effective and safe therapeutic option in patients with ACEi‐induced angioedema, which needs to be confirmed by further larger and double‐blinded studies. Level of Evidence 4. Laryngoscope, 125:E198–E202, 2015